Clinical, microscopic and imaging findings associated to Mccune-Albright syndrome: report of two cases - Xavier,Samuel Porfírio (2008)
McCune-Albright syndrome is characterized by the triad café-au-lait cutaneous spots, polyostotic fibrous dysplasia and endocrinopathies. This article presents two cases of McCune-Albright syndrome in a middle-aged woman and a young girl. Both patients presented café-au-lait spots on the face and other parts of the body and expansion of the mandible with radiopaque-radiolucent areas with ground-glass radiographic appearance, and were diagnosed as having fibrous dysplasia and endocrine disorders. The patient of Case 1 had fibrous dysplasia on the upper and lower limbs, thorax, face and cranium, early puberty, hyperglycemia, hyperthyroidism and high serum alkaline phosphatase levels. The patient of Case 2 presented lesions on the upper limbs and evident endocrine disorders. In both cases presented in this article, the initial exam was made because of the mandibular lesion. However, a diagnosis of fibrous dysplasia must lead to investigation of the involvement of other bones, characterizing polyostotic fibrous dysplasia, which is manifested in a number of diseases. An accurate differential diagnosis is mandatory to determine the best treatment approach for each case.